Analysis of Social Media Usage in Enhancing Parental Participation in Child Education - Sunarso, Budi; Mahardhani, Ardhana Januar; Tusriyanto; Suherlan; Ausat, Abu Muna Almaududi (PT. LITERASI SAINS NUSANTARA, 2024)
Child education is a crucial aspect in shaping the character and quality of human resources in the future. Parents play a crucial role in supporting the process of their children's education, both within and outside the school environment. This research aims to conduct a comprehensive analysis of the use of social media by parents and the extent to which it can enhance their involvement in child education. The study employs a qualitative literature review method with a focus on the analysis of literature obtained from Google Scholar. A qualitative approach is utilized to understand the phenomenon deeply and contextually, providing a more comprehensive insight. The study results indicate that social media has brought positive changes in how parents engage in the development of their children. By providing easily accessible communication platforms and various educational information, social media opens the door for more active and informed parental involvement.